Slip transmission of high angle grain boundaries in body-centered cubic metals: Micropillar compression of pure Ta single and bi-crystals. (1st September 2018) - Weaver, Jordan S.; Li, Nan; Mara, Nathan A.; Jones, David R.; Cho, Hansohl; Bronkhorst, Curt A.; Fensin, Saryu J.; Gray, George T.
Abstract: Here we seek to probe and understand the mechanical behavior of grain boundaries in pure Ta as a model bcc material using micropillar compression experiments. Three high angle grain boundaries are chosen with varying crystal orientations. Multiple bi-crystal pillars are prepared containing a single, nearly vertical grain boundary in the approximate center of the pillar and compared against their single crystalline pillar counterparts. The main phenomenon of interest was slip transmission or strain transfer in the bi-crystals which was considered to occur when slip traces aligned across the grain boundary. This occurred in two of the three bi-crystals. These observations were compared against two slip transmission factors, m ' = cos ( ψ ) cos ( κ ) and L R B = cos ( θ ) cos ( κ ), where ψ, θ, a n d κ are the angles between the slip vectors, slip plane normals, and the intersection of the slip planes with the grain boundary from the slip systems on either side of the grain boundary. Additionally, transmission was compared against the stress-strain response and overall deformation (i.e., sheared boundary) of the bi-crystal. The transmission factors exhibited a consistent behavior with slip transmission occurring for high transmission factors and not occurring for low transmission factors. For example, slip transmission occurred for m ' ≥ 0.85 and did not occur for m ' ≤ 0.46. The engineering stress-strain response and overall deformation behavior did not show correlations with the presence or absence of slip transmission. High angle boundaries in bcc metals are shown to represent a diverse set of responses in bi-crystalline micropillar compression experiments. Graphical abstract: Image 1